Methods of improving the efficiency of monitoring of channel deformations of mountain rivers near built-in settlements: on the example of the Buktyrma river - Taukenov, Talgat; Dzhanaleeva, Kulchikhan; Yerzhanova, Zhuldyz (Geodesy and Cartography, 2018)
The results of research on the development of methods for increasing the efficiency of monitoring the channel deformations of mountain rivers using the methods of aerospace studies of the Earth and geoinformation systems are presented. Examples are given of estimating channel deformations, compiling morphological characteristics of the valley, floodplain and river bed, determining the scheme for the development of channel processes using public space imagery, scientific justification for erosion control measures.